Transcriptome analysis and identification of genes associated with floral transition and fruit development in rabbiteye blueberry (Vaccinium ashei) - Xuan Gao; Lida Wang; Hong Zhang; Bo Zhu; Guosheng Lv; Jiaxin Xiao (PLoS ONE, 2021)
Flowering and fruit set are important traits affecting fruit quality and yield in rabbiteye blueberry (Vaccinium ashei). Intense efforts have been made to elucidate the influence of vernalization and phytohormones on flowering, but the molecular mechanisms of flowering and fruit set remain unclear. To unravel these mechanisms, we performed transcriptome analysis to explore blueberry transcripts from flowering to early fruit stage. We divided flowering and fruit set into flower bud (S2), initial flower (S3), bloom flower (S4), pad fruit (S5), and cup fruit (S6) based on phenotype and identified 1,344, 69, 658, and 189 unique differentially expressed genes (DEGs) in comparisons of S3/S2, S4/S3, S5/S4, and S6/S5, respectively. There were obviously more DEGs in S3/S2 and S5/S4 than in S4/S3, and S6/S5, suggesting that S3/S2 and S5/S4 represent major transitions from buds to fruit in blueberry. GO and KEGG enrichment analysis indicated these DEGs were mostly enriched in phytohormone biosynthesis and signaling, transporter proteins, photosynthesis, anthocyanins biosynthesis, disease resistance protein and transcription factor categories, in addition, transcript levels of phytohormones and transporters changed greatly throughout the flowering and fruit set process. Gibberellic acid and jasmonic acid mainly acted on the early stage of flowering development like expression of the florigen gene FT, while the expression of auxin response factor genes increased almost throughout the process from bud to fruit development. Transporter proteins were mainly associated with minerals during the early flowering development stage and sugars during the early fruit stage. At the early fruit stage, anthocyanins started to accumulate, and the fruit was susceptible to diseases such as fungal infection. Expression of the transcription factor MYB86 was up-regulated during initial fruit development, which may promote anthocyanin accumulation. These results will aid future studies exploring the molecular mechanism underlying flowering and fruit set of rabbiteye blueberry.